Gravimetric determination of soil organic matter - Miyazawa, M.; Pavan, M.A.; Oliveira, E.L. de; Ionashiro, Massao [UNESP]; Silva, A.K. (Brazilian Archives of Biology and Technology, 2000)
Avaliou-se o método de determinação gravimétrica da matéria orgânica do solo pela perda de massa por incineração a 300ºC e comparou-se com o carbono determinado pelo método Walkley-Black. Os dois métodos foram correlacionados positivamente com a seguinte equação de regressão linear: y = 3,720x + 0,2914. r = 0,937. O coeficiente. 3,720 foi maior do que os encontrados na literatura. que variaram de 1,68 a 2,13. Esta diferença foi atribuída ao maior grau de oxidação da matéria orgânica dos solos das regiões tropicais. O método de incineração é aplicável para determinação do C do solo em rotina. O método não contamina o meio ambiente com metal tóxico (Cr6+) e não oferece riscos aos analistas com o uso de ácido sulfúrico concentrado.

Studies were carried out to evaluate a gravimetric method for the determination of soil organic matter by the mass loss at 300ºC. The gravimetric method was compared with Walkley-Black, using several brazilian soils with variable chemical and physical properties. Gravimetric method was positively correlated with Walkley-Black method with the following linear regression equation: y = 3.72x + 0.29, r = 0.94. The angular coefficient 3.72 for tropical soils was greater than those reported in the literature for temperate soils (from 1.68 to 2.13). The difference was due to greater oxidation degree of the organic matter. When compared with Walkley-Black method, gravimetric technique showed certain distinct advantages such as no environmental contamination with Cr6+ and improved laboratory safety eliminating the use of concentrated sulfuric acid.
Keywords: organic carbon; thermogravimetry; soil analysis